2009
DOI: 10.1007/s11055-009-9160-4
|View full text |Cite
|
Sign up to set email alerts
|

Cortical-Subcortical Interactions and the Regulation of the Functional State of the Brain in Acute Hypoxia in Humans

Abstract: The mechanisms regulating the functional state (FS) of the brain were studied in humans in conditions of dosed acute hypoxia (breathing a mixture of 8% oxygen in nitrogen for 15-25 min). The dynamics of the FS of the brain due to changes in the balance of the activities of brain regulatory structures in hypoxia were reflected in rearrangements of EEG spatial relationships (factor and cluster analysis of EEG crosscorrelation matrixes) and the redistribution of intracerebral locations of electrically equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…Normobaric hypoxia was administered in the form of a lowered fraction of inspired O 2 (F I O 2 = 0.08) to participants for 15–25 min (S p O 2 ≤75%). In line with the EEG-hypoxia literature, it was found that the acute exposure to hypoxia was accompanied by slowing and synchronisation of the EEG signals (50). Such a reduction and synchronisation of the EEG signal was said to characterise a functional brain state that was relatively lower compared to baseline (i.e.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…Normobaric hypoxia was administered in the form of a lowered fraction of inspired O 2 (F I O 2 = 0.08) to participants for 15–25 min (S p O 2 ≤75%). In line with the EEG-hypoxia literature, it was found that the acute exposure to hypoxia was accompanied by slowing and synchronisation of the EEG signals (50). Such a reduction and synchronisation of the EEG signal was said to characterise a functional brain state that was relatively lower compared to baseline (i.e.…”
Section: Introductionsupporting
confidence: 53%
“…Due to the differences in the severity and time of hypoxic exposure or methods utilised, direct comparisons between previous investigations are difficult to make. However, it does seem that the greatest change in EEG occurs at a similar S p O 2 or oxygen tension (PO 2 ) (≤75% or ≤40 mmHg; 35, 44, 48, 50). Nevertheless, such slowing of the EEG signal might reflect the previously discussed widespread depolarisation of cerebral neurons known to occur in AH.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations